PROGRAM CERIA DALAM PENCEGAHAN ANEMIA REMAJA PUTRI SMKS KESEHATAN DARUSSALAM LHOKSEUMAWE - Nurmi, Nurmi; Siswanto Pabidang; Yustina Ananti (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2026)
Anemia among adolescent girls remains a public health problem that affects reproductive health and quality of life in adulthood. The CERIA Program (Cegah Anemia Remaja melalui Edukasi Tablet Tambah Darah) was implemented as a community service activity to improve knowledge and awareness of anemia and iron tablet consumption among adolescent girls. This program was conducted at SMKS Kesehatan Darussalam Lhokseumawe using interactive health education methods, including lectures, discussions, and simple printed media. Evaluation was carried out using pre-test and post-test assessments of knowledge and a participant satisfaction survey. The results showed that before the intervention, most participants had moderate (40.0%) and low (30.0%) levels of knowledge. After the educational intervention, the majority of respondents achieved a good level of knowledge (73.3%), with no participants remaining in the low category (0.0%). Furthermore, the satisfaction survey indicated that all participants (100%) provided positive evaluations, reflecting a good level of satisfaction. The CERIA Program is effective in improving knowledge and participant satisfaction and has the potential to support sustainable anemia prevention among adolescent girls.